Entanglement dynamics of an open moving-biparticle system driven by classical-field. (1st May 2022) - Wang, Qilin; Liu, Rongfang; Zou, Hong-Mei; Long, Dan; Wang, Jia
Abstract: In this work, the entanglement dynamics of a moving-biparticle system driven by an external classical field are investigated, where the moving-biparticle system is coupled with a zero temperature common environment. The analytical expressions of the density operator and the entanglement can be obtained by using the dressed-state basis when the total excitation number is one. We also discuss in detail the effects of different parameters on the entanglement dynamics. The results show that the classical driving can not only protect the entanglement, but also effectively eliminate the influence of the qubit velocity and the detuning on the quantum entanglement.